Reliability of a high-intensity cycling capacity test - Saunders, B.; Sale, C.; Harris, R. C.; Morris, J. G.; Sunderland, C. (Journal of Science and Medicine in Sport, 2013)
Objectives To assess the reliability of the CCT110%, a high-intensity cycling capacity test performed to exhaustion. Design 27 recreationally active participants (age 23 ± 4 y; height 1.79 ± 0.06 m; body mass 78.0 ± 8.8 kg; Powermax 306 ± 49 W) performed the CCT110% on two occasions. Methods Performance measures determined from the CCT110% were time to exhaustion (TTE) and total work done (TWD). Blood pH, lactate, bicarbonate and base excess were determined before exercise, immediately after exercise, and 5 min after exercise. Exercise capacity data were analysed using intra-class correlations (ICC), systematic bias ratio, ratio limits of agreement, coefficient of variation (CV) and t-tests. Blood variables were analysed using repeated measures ANOVA and Tukey tests for post hoc comparisons. Results TTE (mean ± SD: 134 ± 20 s and 135 ± 20 s, P = 0.75) and TWD (42.2 ± 10.3 kJ and 42.2 ± 9.8 kJ, P = 0.97) were not different between trials. The ICC between trials was r = 0.88 for TTE and r = 0.94 for TWD, with the CV being 4.43% for TTE and 4.94% for TWD. There were no between trial differences in blood markers at any time point except immediately post-exercise pH (7.246 ± 0.041 vs. 7.269 ± 0.064, P = 0.004). Conclusions The CCT110% is a reliable exercise protocol that can be used for nutritional interventions designed to affect intracellular and extracellular pH changes. Although blood pH was significantly different between trials immediately post-exercise, the absolute differences are much smaller than those expected to be seen using nutritional interventions intended to alter extracellular pH during exercise.